PENDAMPINGAN PEMANFAATAN DAUR ULANG SAMPAH SEBAGAI MEDIA PEMBELAJARAN DI MASA COVID-19 DI RA AS-SABROWI LEDOKOMBO JEMBER - Elok Rufaiqoh; Nurul Iflaha; Badrus Sholeh (Lembaga Penelitian, Publikasi Ilmiah dan Pengabdian kepada Masyarakat (LP3M), 2021)
Every teacher is required to be creative and innovative, so that learning is more meaningful and students do not feel bored, especially during a pandemic like today. The purpose of this service activity is to provide knowledge to the teacher of RA As-Sabrowi Suren Ledokombo Jember about the use of waste recycling into creative, innovative and simple learning media. The method used is based on Asset Basic Community Development (ABCD). The steps for this method are as follows: 1) Define; Determine the aspects that will be the benchmark for the assisted process, 2) Discovery; In-depth discovery, in this case empowerment carries out an in-depth search process such as finding and detecting 5 assets owned by the community in RA As-Sabrowi, 3) Dreams; is a step in order to achieve the goals or desires that will be achieved during the assistance, 4) Design; this process has entered the stage of the strategy to be used, 5) Deliver; implement and evaluate all aspects of the lack of waste recycling utilization into creative, innovative and simple learning media. The results that have been carried out in the field are: a) The development of the quality of human resources for RA As-Sabrowi teachers is running effectively or in accordance with the goals that have been set. The teachers of RA As-Sabrowi already know, understand and are proficient in utilizing waste recycling as an effective, innovative and simple learning medium; b) Learning media and learning resources are getting more and more varied at RA As-Sabrowi.